2018
DOI: 10.15376/biores.13.2.4484-4496
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Pyrolysis Characteristics of Enzymatic/Mild Acidolysis Lignin (EMAL)

Abstract: Fast pyrolysis is a promising method that is being investigated for application in the degradation of lignin into phenolic chemicals. In this study, enzymatic/mild acidolysis lignin (EMAL) isolated from eucalyptus (E-EMAL) and wheat straw (W-EMAL) were characterized by pyrolysisgas chromatography/mass spectrometry. The results showed that the compositions and yields of the products were determined by the lignin type and pyrolysis temperature. The identified products from the E-EMAL and W-EMAL pyrolysis mainly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 38 publications
0
12
0
1
Order By: Relevance
“…Li et al compared the pyrolysis of wood and herbaceous EMAL and found that a high phenolics yield can be obtained at mild pyrolysis temperatures of 450 to 650°C. [85] The enzyme was also used in further fractionation of the lignin. For example, two common lignins (alkaline lignin: AL, and hydrolysis lignin: HL) were treated with laccase, and the results show that the structure, especially the Ph-OH contents and molecular weight of lignin, could be effectively controlled, which is beneficial for antioxidation applications.…”
Section: Enzyme-assisted Fractionationmentioning
confidence: 99%
See 1 more Smart Citation
“…Li et al compared the pyrolysis of wood and herbaceous EMAL and found that a high phenolics yield can be obtained at mild pyrolysis temperatures of 450 to 650°C. [85] The enzyme was also used in further fractionation of the lignin. For example, two common lignins (alkaline lignin: AL, and hydrolysis lignin: HL) were treated with laccase, and the results show that the structure, especially the Ph-OH contents and molecular weight of lignin, could be effectively controlled, which is beneficial for antioxidation applications.…”
Section: Enzyme-assisted Fractionationmentioning
confidence: 99%
“…This strategy is usually used in laboratory research. Li et al compared the pyrolysis of wood and herbaceous EMAL and found that a high phenolics yield can be obtained at mild pyrolysis temperatures of 450 to 650 °C . The enzyme was also used in further fractionation of the lignin.…”
Section: Fractionation From Lignocellulosic Biomassmentioning
confidence: 99%
“…During pyrolysis, G-type phenols can be gradually transformed into H-type ones due to the enhanced cleavage of methyl aryl ether bond caused by DES treatment. On the other hand, a small amount of mono aromatic hydrocarbons (MAHs) can also be observed, formed via secondary reactions, such as dehydroxylation and demethoxylation at high temperatures [ 234 ]. In addition, compared to untreated lignin, DES-treated samples can produce more MAHs due to their improved hydrogen to carbon efficient ratio (i.e., H/C eff ) [ 235 ].…”
Section: Lignin Pyrolysismentioning
confidence: 99%
“…Over one million tons of lignin are produced per year as a byproduct of the paper and pulp industry, and this value is poised to increase from the emerging biomass refinery industry (Glasser et al 1999). Only approximately 2% of the lignin available from the pulp and paper industry is used commercially, with the remainder being burned as a low-value fuel (Lou et al 2010).…”
Section: Introductionmentioning
confidence: 99%